The Influence of Robotic Process Automation on the Administrative Workload of Teachers (Open International Journal of Informatics, 2024)
Teachers often encounter a massive volume of administrative tasks that may affect their productivity and overall satisfaction with their work. Due to excessive workloads, teachers may encounter high levels of stress and a decline in the quality of their teaching. An advanced solution technique that incorporates Robotic Process Automation (RPA) offers a possible resolution to optimize teachers’ workload. Therefore, this study investigates the influence of RPA in optimizing administrative workload and job satisfaction. Moreover, this study has the goal of identifying key considerations and challenges in developing RPA projects within educational settings. The research included a sample of 30 teachers selected from several schools, ensuring a diverse sample in terms of experience, subject specialization, and school type which are public and private. The surveys are conducted to allow for a comprehensive understanding of the varying impacts and perceptions of RPA across different educational contexts. The results demonstrate a significant integration of RPA in terms of minimizing administrative workload, challenges of adaptation, enhanced job satisfaction, and increased efficacy and productivity. Teachers also expressed a greater positive impact of the implementation of RPA with 76.7% influence on interaction with students and 46.7% able to improve job satisfaction. The integration of RPA into administrative workload not only streamlines administrative tasks but also allows teachers to dedicate more time to instructional and student-centered activities. Future research could focus on long-term impacts and exploration of RPA across different educational contexts.
Keywords: Robotic Process Automation; Informatics; Job satisfaction; Education